Food oxidants and antioxidants chemical, biological, and functional properties - Bartosz, G. (CRC Press, 2014)
"This volume discusses the effects of naturally occurring and process-generated pro-oxidants and antioxidants on various aspects of food quality. It emphasizes the chemical nature and functional properties of these compounds and their interactions with other food components in storage and processing, specifically focusing on the sensory quality, nutritional value, health promoting activity, and safety aspects of foods. It demonstrates the analysis of pro-oxidants and antioxidants in foods, their mechanism and activity, their chemistry and biochemistry, and the practical considerations of healthy food production and marketing"-- Provided by publisher.
Keywords: Food additives.; Oxidizing agents.; Antioxidants.; elektronické knihy; electronic books